2013
DOI: 10.1164/rccm.201206-1117cp
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Respiratory Muscles in the Critically Ill

Abstract: Evidence has accumulated that respiratory muscle dysfunction develops in critically ill patients and contributes to prolonged weaning from mechanical ventilation. Accordingly, it seems highly appropriate to monitor the respiratory muscles in these patients. Today, we are only at the beginning of routinely monitoring respiratory muscle function. Indeed, most clinicians do not evaluate respiratory muscle function in critically ill patients at all. In our opinion, however, practical issues and the absence of soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
157
1
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 60 publications
0
157
1
15
Order By: Relevance
“…Diaphragmatic dysfunction in patients receiving mechanical ventilation most frequently occurs relatively symmetrically secondary to neuromuscular disorders or non-myopathic diseases such as chronic obstructive pulmonary disease, to ICU-acquired neuromyopathy and/ or to ventilator-induced diaphragmatic dysfunction [31][32][33]. Alternatively, phrenic nerve injury, especially during cardiac surgery, may lead to asymmetric diaphragmatic dysfunction [34].…”
Section: Assessment Of Diaphragmatic Functionmentioning
confidence: 99%
“…Diaphragmatic dysfunction in patients receiving mechanical ventilation most frequently occurs relatively symmetrically secondary to neuromuscular disorders or non-myopathic diseases such as chronic obstructive pulmonary disease, to ICU-acquired neuromyopathy and/ or to ventilator-induced diaphragmatic dysfunction [31][32][33]. Alternatively, phrenic nerve injury, especially during cardiac surgery, may lead to asymmetric diaphragmatic dysfunction [34].…”
Section: Assessment Of Diaphragmatic Functionmentioning
confidence: 99%
“…The gold standard for the diagnosis of bilateral diaphragmatic paralysis is the measurement of the transdiaphragmatic pressure (Pdi) [7,10]. This is the difference between abdominal and esophageal pressure during maximal voluntary contraction or upon electrical or magnetic stimulation (twitch Pdi) [10,11,12,13]. Due to the invasive nature of this test and the technical challenges involved in collecting reliable results [14], this technique is restricted to a limited number of clinics and laboratories and it has achieved only limited application in clinical practice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Methods to assess diaphragmatic dysfunction are difficult to implement in daily clinical practice, especially in ICU patients due to their poor bedside enforceability, low diagnostic accuracy, and the invasiveness of certain techniques (6). Several studies reported the feasibility and accuracy of bedside ultrasound evaluation of diaphragm thickness (i.e., atrophy) and function (7)(8)(9)(10).…”
mentioning
confidence: 99%